The role of hira mountain in the life of the prophet(PBUH) - Ahmed, Khatab I. (Humanities Journal of University of Zakho, 2015)
This research aims to study and clarify the importance of Hira mountain in the life of the prophet (pbuh), the place which he was physically and spiritually connected to. Before the holy prophetic mission, people used to visit the Hira cave each year for worshipping. It was in the month of Ramadan which approves the revelation of the Qur,an. As Allah asid (Month of Ramadan which revealed the Qur,an…). The descending of Gabrial (puh) from the top of Hira ,s mountain which marked a strong bond to prophet (pbuh) because even a fter the mission he was meeting his companions or some who were chosen to meet him on that mountain It is located in the north-east of Mecca, three miles away, In one of the prophets meetings (pbuh) with his companions, the mountain moved, and the prophet ordered it to stay still, Thus it did so. In addition to other incidents which happened to prophet (pbuh) on that high mountain, such as Gabrial who read Selam on Khajija. Also, Gabrial (puh) has taught the prophet (pbuh) how to do ablution and establish prayer on this mountain. The revelation of Gabrial (puh) to the prophet (pbuh) on the top of Hira mountain and witnessing the "Mursalat Sura" on the prophet by the companion Abdulla Masoud. The polytheists asked the prophet (pbuh) to split the moon into parts for them. So, God split the moon into two parts. o, God split the moon into two parts. Even the people saw the Hira Mountain between its two parts. Also when the prophet went to Taif in tenth year of the mission for distributing the call, the people of Talso when the prophet went to Taif in tenth year of the mission for distributing the call, the people of Taif refused his call. After that, he came to Hiras mountain to negotiate with the leaders of Mecca. In one night, the prophets companions lost the prophet (pbuh), and they were afraid that something might have happened to him . So, they went out looking for him, when they saw him coming from Hiras mounting . So, the prophet (pbuh) was connected to Hiras and was always going to it in any problem or predicament.